1975
DOI: 10.1044/jshr.1801.82
|View full text |Cite
|
Sign up to set email alerts
|

Language Performance of Educable Mentally Retarded and Normal Children at Five Age Levels

Abstract: The present study comprised an analysis and comparison of the language performance of educable mentally retarded and normal children at mental age levels six through 10 years. Both syntactic and functional performance variables were investigated. The results indicate language performance differences between the two groups with the primary discriminators being hesitation phenomena (false starts, filled pauses, and repeats) and clausal constructions (relative and subordinate clauses), resulting in a higher sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Upon reexamination of the literature, it became apparent to the present authors that most of the research on grammatical morphemes in the mentally retarded employed controlled observation procedures based upon Berko's (1958) test that are known to underestimate level of mastery when compared with data derived from speech samples (e.g., Dever, 1972). Furthermore, it is not clear that mentally retarded individuals' mastery of complex sentence structures has been adequately assessed in the literature (see, for example, Naremore & Dever, 1975).…”
mentioning
confidence: 94%
“…Upon reexamination of the literature, it became apparent to the present authors that most of the research on grammatical morphemes in the mentally retarded employed controlled observation procedures based upon Berko's (1958) test that are known to underestimate level of mastery when compared with data derived from speech samples (e.g., Dever, 1972). Furthermore, it is not clear that mentally retarded individuals' mastery of complex sentence structures has been adequately assessed in the literature (see, for example, Naremore & Dever, 1975).…”
mentioning
confidence: 94%
“…The answer depends heavily upon having a realistic concep.tion of what language capabilities the retarded child has and what they should next learn (Naremore and Dever, 1975).…”
Section: )mentioning
confidence: 99%
“…2) comprehension skills exceeding ·expressive skills (Sievers and Essa, 1961;Stra~zula, 1966;Cornwall, 1974;Naremore and Dever, 1975); 3) delay of onset of speech and language development (Karlin and Strazzula, 1952;McCarthy, 1964;Jordan, 1966); 4) syntax and morphological skills below age expectations (Brown and Berko, 1960;. Menyuk, 1964;Palermo, and Jenkins, 1964); 5) significantly lower levels of performance in skills of categorization and concept usage (Stephens, 1963;Blount, 1967); 6) limited ability to use abstract language (Karlin and Strazzula, 1952;Strazzula, 1966;Jordan, 1967); and 7) general developmental lags in language development and/or disordered language development (Wewetzer, 1959;Spreen, 1965;Semmel et al, 1968).…”
Section: Language Of the Retardedmentioning
confidence: 99%
“…The production of complex sentence forms by children with mental retardation has also been studied. Generally, these forms have not been the principal target of investigation, but rather are included in studies of a range of syntactic forms (e.g., Bliss, Allen, & Walker, 1978;Graham & Graham, 1971;Lozar, Wepman, & Hass, 1973;Naremore & Dever, 1975; for review, see Rosenberg, 1982;Rosenberg & Abbeduto, 1993). In general, these studies have suggested that the productive language of persons with retardation resembles the productive language of typically developing persons at similar cognitive levels of development.…”
mentioning
confidence: 99%
“…Subjects classified as trainable produced no correct embedded sentences. Naremore and Dever (1975) examined the language production of typically developing children at 6, 7, 8, 9, and 10 years of age and children with retardation with corresponding mental ages. Comparisons at the 10-yearold level revealed differences in the production of subordinate clauses, relative clauses, and predicate elaboration, with typically developing children producing higher rates of each.…”
mentioning
confidence: 99%